The relationship between emotional regulation difficulties and subjective well-being in children aged 6-7 years - Anik Indarwati; Martini Jamaris; Elindra Yetti (AOSIS, 2019)
A number of studies have shown the relationship between emotional regulation difficulties and subjective well-being. Reappraisal is considered a form of emotional regulation better than suppression. However, suppressing emotional expression increases the activity of physiological responses which actually harms the human health in the long run. Early age children still have difficulty in regulating their emotions, and this is likely to affect their psychological well-being if not properly managed . This study aims to examine the relationship between emotional regulation difficulties and subjective wellbeing in children aged 6-7 years. Study participants (N = 55) were children in their early childhood who were transitioned from kindergartens to Gorontalo elementary school. Data were obtained through questionnaires using an Emotional Regulation Checklist / ERC (shiedls & ciccheti, 2003) and subjective welfare questionnaire. Based on data analysis using Pearson product moment correlation test, the researcher found that the correlation coefficient (rxy) is 0.408 with p = 0.000 (p < 0.01). This indicates that there is a significant negative relationship between the variable of the value of emotional regulation difficulties with subjective wellbeing.